Marginalized : Indian poetry in English (DQR studies in literature, 2014)
This book illustrates and debates the well-grounded and confident tradition of Indian Poetry in English. It contains individual essays on poets before and since the Indian Independence focus on the poetry of Derozio, Tagore, Aurobindo and Naidu right down to the modern and contemporary poets like Ezekiel, Mahapatra, Ramanujan, Kolatkar, Das, Moraes, Daruwalla, de Souza, Jussawalla and Patel who ushered in a change both in terms of subject matter and style.